THE JUST REGULATION OF IMMATERIAL LOSSES IN SHARIA ECONOMIC DISPUTES: RECONSTRUCTION OF TA'WID BASED ON MAQASID AL-SYARI'AH - Tiya Ulfa; Sukarmi; Nur Chanifah (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This article examines the regulation of immaterial losses in sharia economic disputes and proposes a reconstruction through maqashid al-syariah as an analytical tool. The normative basis for compensation has been recognized through the concepts of ta'wid and daman in the Compilation of Sharia Economic Law (KHES) and the DSN-MUI fatwa, but this formulation stops at the principle and interprets "real losses" primarily as nominal costs. This study uses normative legal research methods with statutory, conceptual, and historical approaches. The first finding shows that a narrow reading of the term "real" is not a neutral stance, but rather creates a double maqashid deficit: on the one hand, the law only restores hifz al-mal and ignores hifz al-nafs , hifz al-'aql , and hifz al-'ird ; on the other hand, the lack of norms encourages judges to borrow general civil law without a sharia filter, thereby opening up the risk of gharar and unlawful enrichment. The second finding offers an ideal regulatory model that redefines “real” functionally, recognizes immaterial losses in a limited and measurable manner within the paradigm of recovery ( jabr al-darar ), maps four categories of losses to the maqashid they protect, establishes thresholds based on the hierarchy of darurriyyat–hajiyyat–tashiniyyat and the principle of proportionality, and designs layered evidence and guided discretion. The novelty of this article lies in providing an operative framework for immaterial losses guided by maqashid, which has not been provided by KHES, fatwas, or previous studies. The most realistic update is carried out through strengthening KHES within the framework of PERMA, affirmation of DSN-MUI, and the Supreme Court's technical guidelines for Religious Court judges.